2011
DOI: 10.3892/ijmm.2011.658
|View full text |Cite
|
Sign up to set email alerts
|

Cocktail therapy with a combination of interferon, ribavirin and angiotensin-II type 1 receptor blocker attenuates murine liver fibrosis development

Abstract: Abstract. An effective therapeutic strategy for suppressing liver fibrosis development should improve the overall prognosis of patients with chronic liver diseases. Despite efforts to develop anti-fibrotic agents, no drugs have yet been approved as anti-fibrotic treatments for humans. An alternative strategy may be to employ a clinically available agent that also exhibits anti-fibrotic activities, for which the safety of long-term administration has been proven. The aim of the current study was to elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…We previously demonstrated that blockade of angiotensin-II (AT-II) signal transduction through AT-II type 1 receptor (AT1R) inhibited hepatic fibrogenesis in rats [11,12]. The inhibitory effects of ARB mostly coincided with the suppression of activated hepatic stellate cells (Ac-HSC) [13]. Moreover, we demonstrated AT-II augmented LPS-TLR4 signaling through AT1R and ARB improved hepatic fibrogenesis and reduced TLR4-mediated innate immune signaling in Ac-HSC [14].…”
Section: Introductionmentioning
confidence: 89%
“…We previously demonstrated that blockade of angiotensin-II (AT-II) signal transduction through AT-II type 1 receptor (AT1R) inhibited hepatic fibrogenesis in rats [11,12]. The inhibitory effects of ARB mostly coincided with the suppression of activated hepatic stellate cells (Ac-HSC) [13]. Moreover, we demonstrated AT-II augmented LPS-TLR4 signaling through AT1R and ARB improved hepatic fibrogenesis and reduced TLR4-mediated innate immune signaling in Ac-HSC [14].…”
Section: Introductionmentioning
confidence: 89%
“…HSYA interrupted ERK5 signaling in culture-activated HSC by reducing the phosphorylation of ERK5 and its downstream MEF2C gene, leading to the inhibition of HSC activation. An effective therapeutic strategy for suppressing liver fibrosis should improve the overall prognosis of patients with chronic liver diseases (Yoshiji et al, 2011). At this time, there is no ideal drug therapy for hepatic fibrosis (Pradeep Kumar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(14,15) This inhibitory effect of AT1R blocker (ARB) mostly coincided with the suppression of activated-HSCs (Ac-HSCs). (16) Accordingly, combined INT747 and ARB treatment might be useful in NASH. Here, we evaluated the effect and possible underlying mechanisms of combined INT747 and ARB administration on hepatic fibrogenesis in two different NASH rat models.…”
Section: Numerous Pharmaceutical Companies Have Beenmentioning
confidence: 99%